Estudo da modulação farmacológica do efeito enterotoxico induzido pela toxina A do Clostridium difficile em ileo de coelho - Menezes, Antonio Teles de (2002)
Clostridium difficile is an anaerobic bacterium present at human and domestic animais intestinal microbiota. This microorganism is recognized to be responsible for an antibiotic-associated pseudomembranous colitis coinmonly in patients under an intense long- term antimicrobial therapy. Several proinflammatory events induced by its toxins A and B are not clear yet. On the other hand, many reports have been demonstrated a better comprehension about those mechanisms The aim of this work was to investigate the enterotoxic effects induced by Clostridium. difficile toxin A in rabbit ileum. The experimental model used was ligated intestinal loops, in vivo which male and female New Zeland rabbits (1.5-2.5 kg) were fasted 24 hours before the experiments with water ad libitum only. Animais were euthanized to recover the intestinal fluid and determine the intestinal secretion rate by fluid volume (pl) over loop length (cm), expressed in pl/cm. After dose and time-effect curves plotting, other groups of animais were pretreated using many anti- inflammatory drugs. The data has been shown as mean ± SEM and analyzed by ANOVA (Bonferroni test). Results demonstrated increase in intestinal secretion rates since the dose of l.Opg/ml (TxA=l070,7 ± 122,9 pl/cm Vs PBS=95,9 ± 44,9 pl/cm; p<0,05; n=16) as well as in time of 12 hours (TxA= 673,6 ± 118,11 pg/ml; n= 10; p<0,05) after toxin A injection, it obtaining maximal effect in 18 hours (TxA= 1070,7 ± 122,90 pl/cm, n=12; p<0,05). Dexametasone, a classical anti-inflammatory drug was able to block secretion sigmficantly (DEXA= 172,3 ± 37,0 Vs. TxA 1034,9 ± 93,0 pl/cm; n = 15; p<0,05; 83%). Celecoxib, on the other hand, blocked 56% of intestinal secretion rate. It was also demonstrated that leukotriens do not participate, effectively, in the secretory events because the treatment with montelucaste sodico did not alter the secretion rate (MONTE= 702.2 ± 106,4 Vs TxA 1034.9 ± 93,0 pl/cm). The pretreatment with association involving two anti-inflammatory drugs did not contribute to pharmacological synergism increase boped. It had driven to partial blockage in the studied groups with indomethacin and celecoxib (INDO + CELOX= 421,7 ± 60,0 Vs. TxA 1034,9 ± 93,0 pl/cm; n — 13) and celecoxib + pentoxifyline (PENTOX + CELOX= 539,7 ± 76,5 Vs. TxA 1034,9 ± 93,0 pl/cm; n = 23). ■ Severe tissue-damaging changes were observed into the ileal mucosa structure under many degrees of severity according to the COX-2 selective enzymatic inhibition. Therefore, these data suggest that secretory activity of Clostridium difficile toxin A was a dose and time-dependent process. It was also proposed the effective participation of prostaglandins (as showed in partial blockage featured by COX-2 most selective anti- inflammatory drugs), but not leukotriens, in the secretory activity induced by toxin A. This toxin is capable to promote several damages in intestinal mucosa as villi destruction, neutrophil infiltration and intense increase in the intestinal secretion.